Pelaksanaan Pengelolaan Administrasi Guru Dalam Meningkatan Mutu Pendidikan - Wahyu Setyo Nugroho (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Teacher administration is an important aspect in the implementation of education, because teacher management is a strategic factor that has a big influence on improving the quality of education. The main problem in this research is "is the implementation of teacher administration running effectively? Based on preliminary research, it is known that there are symptoms of ineffective teacher management, which stand out among others in terms of planning, teacher placement, excessive teacher staff and improving teacher welfare. In planning activities, acceptance and selection planning, induction planning, compensation planning, assessment planning, development planning, transfer planning and employment termination planning have not been made. In teacher placement activities outside their field of study expertise, especially in rare fields of study, teacher development and lack of reference to improving the quality of education in schools. Meanwhile, in the field of teacher welfare, there has been no improvement from previous conditions. Moving on from these conditions, the main question asked in this research is: what is the condition of the teacher administration management institutions and how effective are the teacher administration functions. This study uses a qualitative research approach, with several data collection techniques in the form of interviews, observation and documentation studies. The reason for using a qualitative approach is because this observation is carried out on human behavior interacting in the process of managing teacher administration, starting from the implementation of the planning function to termination of employment. With this approach, the writer/researcher also acts as the main research instrument and is involved in the management process, thereby obtaining the necessary data and information from primary sources, both from the human resources department and related agencies as managers or from teachers as managed employees. Based on research findings and the results of the discussion, it is concluded that it does not yet describe conditions that are conducive to improving the quality of education. Meanwhile, the implementation of teacher management does not fully meet the criteria for the effectiveness of teacher management functions.